The Effects of Daily Stress Factors on University Students’ Emotional Clarity and Internet Overuse - Lee , Young Joo (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study is to investigate the effects of everyday stressors on emotional clarity and Internet hyperactivity because the various everyday stressors that college students face as they transition to adults have a significant impact on adolescents’ mental health Methods/Statistical analysis: Everyday stress is categorized into family, friends, heterosexual, values, and economic factors. An exploratory factor analysis was conducted to confirm the constructive validity of each scale, and a confirmatory factor analysis was performed to re-verify the convergence and discriminant validity of the extracted variables. In addition, reliability verification for internal consistency of variables on each scale was verified by using Cronbach’s α coefficient. And a regression analysis was conducted to determine the effects of daily stress on college students’ emotional clarity and Internet overuse. Findings: To examine how the daily stress of college students affects emotional clarity, the daily stress was found to be friends, heterosexual, values, family, and economic factors. Based on the results of factor analysis on stress, the result of analyzing the effect of stress on emotional clarity only the friend factor had a significant effect. The results of the regression analysis to examine how the daily stress of college students affect the overuse of internet are friend factor and the heterosexual factor had a significant effect on internet overuse. However, family, values and economic factors among daily stress types did not have a significant effect on internet overuse. Improvements/Applications: For college students entering adulthood, we found that friend factor is an important factor in daily life and that internet usage increased due to the temporary and instantaneous remedy method. Therefore, it is necessary to make efforts to develop and utilize programs in universities that can recognize their emotions more clearly and to manage and effectively cope with various daily stresses for the health and psychological well-being of college students.